Analyzing Returns Generated on Lumpsum Investments in Select Mutual Fund Schemes (International Journal of Food and Nutritional Sciences, 2022)
With an increasing interest in mutual funds as an investment option, understanding the potential variations in returns across different investment durations becomes crucial for investors seeking to optimize their investment strategies. This research study delves into the examination of significant differences in average annualized returns among various investment periods of mutual fund schemes.To achieve the objectives of this study, the data was collected on the performance of mutual fund schemes over multiple investment periods, ranging from 3 year to 10 years. The sample comprises a diverse set of mutual funds, and includes Lumpsum investments. From the average annualized returns and absolute returns of these schemes, we aimed to identify any statistically significant differences in performance.The statistical analysis involved the use of One-way ANOVA and Descriptive Statistics was used. Additionally, p-values were computed to ascertain the level of significance in the differences observed.The results of the analysis demonstrated intriguing patterns in the performance of mutual fund schemes across various investment durations. Notably, significant differences in average absolute and annualized returns were observed in the examined investment periods. This suggests that the choice of Lumpsum investments can significantly impact the overall returns for certain durations.